下列计算的结果是 x 5 的为 ( )
A. x 10 ÷ x 2 B. x 6 - x C. x 2 ⋅ x 3 D. ( x 2 ) 3
下列计算正确的是 ( )
A. ( a 2 ) 3 = a 5 B. ( - 2 a ) 2 = - 4 a 2 C. m 3 · m 2 = m 6 D. a 6 ÷ a 2 = a 4
A. a + a = a 2 B. ( 2 a ) 3 = 6 a 3 C. ( a − 1 ) 2 = a 2 − 1 D. a 3 ÷ a = a 2
A. x 3 - x 2 = x B. x 3 · x 2 = x 6 C. x 3 ÷ x 2 = x D. ( x 3 ) 2 = x 5
下列运算正确的是 ( )
A. 4 x + 5 y = 9 xy B. ( - m ) 3 · m 7 = m 10 C. ( x 2 y ) 5 = x 2 y 5 D. a 12 ÷ a 8 = a 4
A. a 7 ÷ a 4 = a 3 B. 5 a 2 - 3 a = 2 a C. 3 a 4 · a 2 = 3 a 8 D. ( a 3 b 2 ) 2 = a 5 b 4
A. a 3 + a 2 = a 5 B. a 3 - a 2 = a C. a 3 · a 2 = a 6 D. a 3 ÷ a 2 = a
A. 3 a + 4 b = 7 ab B. ( a b 3 ) 2 = a b 6 C. ( a + 2 ) 2 = a 2 + 4 D. x 12 ÷ x 6 = x 6
A. 5 x - 3 x = 2 B. ( x - 1 ) 2 = x 2 - 1 C. ( - 2 x 2 ) 3 = - 6 x 6 D. x 6 ÷ x 2 = x 4
A. a 2 + a 3 = a 5 B. a 2 · a 3 = a 5 C. a 3 ÷ a 2 = a 5 D. ( a 2 ) 3 = a 5
A. a 2 · a 3 = a 6 B. a 6 ÷ a - 2 = a - 3
C. ( - 2 a b 2 ) 3 = - 8 a 3 b 6 D. ( 2 a + b ) 2 = 4 a 2 + b 2
A. x 2 · x 3 = x 6 B. x 6 ÷ x 3 = x 3 C. x 3 + x 3 = 2 x 6 D. ( - 2 x ) 3 = - 6 x 3
A. 3 a 2 − a 2 = 3 B. ( a 2 ) 3 = a 6
C. a 2 · a 3 = a 6 D. a 6 ÷ a 2 = a 3
A. a 8 ÷ a 4 = a 2 B. ( 2 a 2 ) 3 = 6 a 6
C. 3 a 3 − 2 a 2 = a D. 3 a ( 1 − a ) = 3 a − 3 a 2
A. a 5 + a 5 = a 10 B. a 7 ÷ a = a 6
C. a 3 · a 2 = a 6 D. ( − a 3 ) 2 = − a 6